2017
DOI: 10.3899/jrheum.161078
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Approaches for Withdrawing Drugs for Children with Clinically Inactive Nonsystemic JIA: A Survey of the Childhood Arthritis and Rheumatology Research Alliance

Abstract: Objective To assess the attitudes and strategies of pediatric rheumatology clinicians towards withdrawing medications for children with clinically inactive juvenile idiopathic arthritis (JIA). Methods Members of the Childhood Arthritis and Rheumatology Research Alliance (CARRA) completed an anonymous electronic survey on decision-making and approaches for withdrawing medications for inactive non-systemic JIA. Data were analyzed using descriptive statistics. Results Of 388 clinicians in CARRA, 124 completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…Unfortunately, there is currently a lack of evidence-based data from clinical trials and clinical care and of guidelines to aid in the withdrawal of medications after disease remission in JIA. A recent survey among North American paediatric rheumatologists conducted by the Childhood Arthritis and Rheumatology Research Alliance has shown a large variability in the preferences of medication withdrawal for CID 67. No reliable clinical, biomarker or imaging indicators are currently available to identify patients at higher risk of experiencing disease flare after treatment discontinuation.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there is currently a lack of evidence-based data from clinical trials and clinical care and of guidelines to aid in the withdrawal of medications after disease remission in JIA. A recent survey among North American paediatric rheumatologists conducted by the Childhood Arthritis and Rheumatology Research Alliance has shown a large variability in the preferences of medication withdrawal for CID 67. No reliable clinical, biomarker or imaging indicators are currently available to identify patients at higher risk of experiencing disease flare after treatment discontinuation.…”
Section: Resultsmentioning
confidence: 99%
“…It may reflect the widely used withdrawal strategy in Germany. Withdrawal of MTX first is also the preferred strategy in the USA and Canada [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric rheumatology, more qualitative research has focused on decisions about starting DMARDs, including studies on the perspectives of patients and families (21,23). Prior research about stopping JIA medications has focused on clinicians’ perspectives through interviews and surveys (19,21). Research examining the perspectives of adults with RA on stopping antirheumatic medicines has also highlighted similar tensions between risks of arthritis and risks of treatments, the role of uncertainty and unpredictability, the importance of achieving normalcy, and impacts of prior disease experiences (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers for guiding decisions on treatment withdrawal have been tested (17) but not sufficiently validated for routine clinical use (18). Choices about stopping treatment are further complicated by insufficient data on effective withdrawal strategies (19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation